Nilai dan Makna Pelaksanaan Tradisi Ngerebeg dalam Pembentukan Karakter Generasi Milenial di Desa Tegalalang, Gianyar - Asmariati, Anak Agung Inten (Humanis, 2023)
This study aims to find out What are the character values ??of the Ngerebeg tradition which can be used as a source of  history learning, as well as the meaning of carrying out the Ngerebeg tradition for the Tegalalang Pekraman village community. In this study, data were collected using quantitative methods with the following stages, Determining the research location, determining informants, then data collection methods (observation, interviews, study of documents), then data validity techniques (data triangulation), and finally data processing techniques from data processing is poured into historiography. The results of the study show that, (1) the tradition of Ngerebeg can be used as one of the contents of traditional historical sources called local wisdom for the younger generation or millennial generation including: religious, responsible, disciplined, hard work, creative, nationalist, and social and environmental care. (2) the meaning of the Ngerebeg tradition is believed to be an attempt to neutralize negative traits in humans (sad ripu) ahead of piodalan at Duur Bingin Temple. Sad ripu means six enemies. Ethically, in the management of Hindu religious education, the six enemies must be avoided, shunned, and destroyed